Tinjauan Tafsir Al-Munir terhadap Qs. An-Nisa [4]: 13-14: (Kewarisan Islam Sebagai Indikator Ketakwaan Dan Tanggung Jawab Ukhrawi) - Hany Handayani; Hasan Bakti Nasution (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research discusses Islamic inheritance law with a focus on the wisdom and urgency of obeying the inheritance provisions as stated in QS. An-Nisa verses 13–14. Inheritance is an important aspect of Islamic law because it directly relates to the rights of heirs and justice in the distribution of inherited property. However, its implementation in society often raises problems due to lack of understanding, the influence of customs, and a tendency to ignore Sharia rules. This research aims to analyze the concept of Islamic inheritance, the historical development of inheritance law, as well as the wisdom and urgency of obeying inheritance law based on Wahbah az-Zuhaili's interpretation in Tafsir Al-Munir. The research uses a library research method with a thematic interpretation approach to inheritance verses. The main data sources are the Qur'an and Tafsir Al-Munir by Wahbah az-Zuhaili, while supporting data sources are obtained from hadith, other books of interpretation, and literature related to Islamic inheritance law. The results show that the provisions of inheritance are among Allah's limits (hudud Allah) that must be obeyed. Obedience contains the values of justice, benefit, and protection of rights. Conversely, violation of these provisions can lead to family conflicts and contradicts the goals of Islamic law in realizing social justice